2011
DOI: 10.1089/jmf.2010.0168
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Study and Antimalarial, Antioxidant, and Anticancer Activities ofMelaleuca armillaris(Sol Ex Gateau) Sm Essential Oil

Abstract: This study investigated the chemical composition (by using gas chromatography/flame ionization detection and gas chromatography/mass spectrometry, an antioxidant [1,1-diphenyl-2-picrylhydrazyl] [DPPH] radical-scavenging assay, and a 2,2'-azinobis-3-ethylbenzothiazoline-6-sulfonate [ABTS] radical cation-scavenging assay) and the antimalarial and cytotoxic activities of essential oil extracted from leaves of Melaleuca armillaris. Thirty-two components representing more than 98% of the total composition of the es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 30 publications
1
19
0
1
Order By: Relevance
“…Other compounds, in a lesser amount, are dihydrocarveol (9.0%) and α-terpineol (7.7%), both oxygenated monoterpenoids. In the literature, Chabir and coworkers [8,9] reported 1,8-cineole (85.8%) as the most abundant compound in M. armillaris. The major compound in the essential oil of M. styphelioides was methyl eugenol (91.1%), a phenolic compound.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other compounds, in a lesser amount, are dihydrocarveol (9.0%) and α-terpineol (7.7%), both oxygenated monoterpenoids. In the literature, Chabir and coworkers [8,9] reported 1,8-cineole (85.8%) as the most abundant compound in M. armillaris. The major compound in the essential oil of M. styphelioides was methyl eugenol (91.1%), a phenolic compound.…”
Section: Resultsmentioning
confidence: 99%
“…Literature reports about M. armillaris remain scarce. GC/MS investigations of its essential oil revealed the presence of 1,8-cineole as the main component [812]. Only little information could be found in the literature about the composition of Melaleuca styphelioides Sm.…”
Section: Introductionmentioning
confidence: 99%
“…24-26 Some of them constitute effective alternatives or complements to synthetic compounds of the chemical industry, without exerting the secondary effects of the latter. 27 As reported earlier, essential oils of the Myrtaceae family are Evaluation of activities against various in vitro biological parameters indicated that the methanol extract, acetone extract and essential oil of M. viminalis possess the highest scavenging activities, followed by the chloroform and ethyl acetate extracts; 3 Salem et al 35 and Chabir et al 9 The antibacterial activity of essential oils and extracts of both M. viminalis and M. armillaris plants were evaluated and found to be effective against the tested bacteria. The highest antimicrobial activity was observed on Gram-positive bacteria.…”
Section: Discussionmentioning
confidence: 83%
“…más ampliamente cultivadas, cuyo AE, aún poco estudiado, debido a la presencia de 1,8-cineol entre sus principales componentes, se transforma en una alternativa terapéutica con prometedoras acciones farmacológicas (Chabir et al, 2011). Se encontró actividad inhibitoria, in vitro, frente a especies bacterianas como Bacillus subtilis, Staphylococcus aureus, Staphylococcus epidermidis, Escherichia coli y Pseudomonas aeuriginosa (Amri et al, 2012).…”
Section: Introductionunclassified